Presenting a structural model for predicting mental disturbance based on time perspective with the mediation of psychological coherence and cognitive flexibility in male and female students - Norouzi, Sara; Bashardoust, Simin; Mojtabaie, Mina (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The aim of this study was to provide a structural model for predicting mental disorders based on time perspective mediated by feelings of psychological cohesion and cognitive flexibility. Methods: The method of the present study was descriptive and the correlational research design was structural equation modeling. The statistical population of this study consisted of all undergraduate students of Islamic Azad University of Tehran who were studying in the academic year 2020-21, from them 387 people were selected by multi-stage cluster sampling. Data were collected using the Depression, Anxiety, Stress Lovibond and Lovibond (1995) Questionnaire ٫Time perspective Zimbardo & Boyed (1999) Questionnaire٫the Feelings of Mental Cohesion Flensburg (2006) Questionnaire, and the Dennis and Vanderwall Cognitive Flexibility Questionnaire (2010). Research data were analyzed using SEM structural equations using Amos software. Results: The results showed٫ among all components of time perspective٫ past negative٫ present fatalistic and feelings of psychological cohesion with positive mental disorders٫ and components future٫ present hedonistic and past positive of time perspective and cognitive flexibility with negative mental disorders٫ is significant (P